Effect of stake priming with complete nutrient solution on cassava root and starch yield - Khanthavong, Phanthasin; Phattarakul, Nattinee; Jamjob, Sansanee; Aye, Tin Maung; Rerkasem, Benjavan (2012)
Low quality of cassava stakes for planting is a major cause that limits cassava growth and productivity. Nutrient contents of the stakes are one possible key factor determining the stake quality. Priming refers to a method to improve the performance of plant propagules, such as seed or cutting, by a pretreatment before planting. This study evaluated the effect of soaking assava stakes in nutrient solution on cassava root yield and quality. The effect of cassava stake priming was evaluated in 5 cassava varieties (Rayong 5, Rayong 7, Rayong 9, Rayong 72, and Kasetsart 50 (KU50)) that were grown in the field with and without soaking stake in a complete nutrients solution. Although stake priming had no effect on above ground biomass, it increased root number and root yield of all cassava varieties except KU50. Stake priming increased root yield by up to 25% and starch yield 30% as compared with without priming. In conclusion, cassava stake priming, by soaking in complete nutrient solution, offers a simple, easy and practical means to improve cassava root as well as starch yield.